Veronica's Artificial Intelligence (AI) Business Communication Strategy Analysis as My Telkomsel Customer Service Case Study of Telkomsel Customers in Bengkulu - Fajri, Farhan; Misnawati, Desy (Jayapangus Press, 2025)
Communication evolves alongside technological advancements, shaping how individuals and businesses interact. One of the most widely adopted innovations in recent years is Artificial Intelligence (AI), which has transformed various sectors, including customer service. This study examines the implementation of Veronika, an AI-powered virtual assistant in the MyTelkomsel application, as part of Telkomsel’s business communication strategy. The findings indicate that Veronika has significantly improved customer service efficiency, increasing response speed by up to 40% and reducing operational burdens on call centers. By integrating AI into digital platforms such as WhatsApp and MyTelkomsel, Telkomsel has enhanced accessibility and service flexibility for its customers. Additionally, Veronika’s adaptation of global AI technology to the local Indonesian context has created a more relevant and user-friendly experience, supporting changes in customer behavior as explained by Technological Determinism Theory. However, despite these advantages, challenges remain, particularly in service personalization and AI’s ability to understand complex queries, which affect user satisfaction. These limitations highlight the need for continuous technological improvements, particularly in Natural Language Processing (NLP) and customer interaction models. This research contributes to the ongoing discussion on AI-driven customer service, offering insights into its strategic benefits and limitations. By addressing existing challenges, companies can further refine AI applications to enhance digital engagement and customer loyalty. Future studies should focus on optimizing AI-human interaction to ensure a seamless, personalized customer service experience.